LncRNA TNRC6C‐AS1 regulates UNC5B in thyroid cancer to influence cell proliferation, migration, and invasion as a competing endogenous RNA of miR‐129‐5p. Issue 10 (12th June 2018) - Hou, Sen; Lin, Qiuyu; Guan, Feng; Lin, Chenghe
Abstract: To investigate the biological functions and regulatory mechanism of lncRNA TNRC6C‐AS1 in thyroid cancer (TC). TNRC6C‐AS1, miR‐129‐5p, and UNC5B expression levels were investigated by qRT‐PCR and Western blot. CCK‐8 assay was conducted to determine cell proliferation, while transwell assay was for inspection of cell migration and invasion. Through bioinformatic analysis, the interactions among TNRC6C‐AS1, miR‐129‐5p, and UNC5B were predicted. Dual luciferase reporter gene assay and RNA pull‐down assay confirmed the predicted target relationships. Tumor xenograft assay was applied to inspect the effect of TNRC6C‐AS1 downregulation on TC development in vivo. TNRC6C‐AS1 and UNC5B were overexpressed, while miR‐129‐5p was underexpressed in TC tissues and cells. TNRC6C‐AS1/ UNC5B downregulation and miR‐129‐5p overexpression could suppress proliferation, migration, and invasion of TC cells as well as inhibit tumorigenesis in vivo. MiR‐129‐5p targeted TNRC6C‐AS1 and UNC5B in TC cells; and UNC5B expression was downregulated by knocking down TNRC6C‐AS1, which competitively bound with miR‐129‐5p. Downregulation of TNRC6C‐AS1 restrained TC development by knocking down UNC5B through upregulating the expression of miR‐129‐5p. Abstract : This study was aimed to investigate the biological functions and regulatory mechanism of lncRNA TNRC6C‐AS1 in thyroid cancer(TC). Downregulation of TNRC6C‐AS1 restrained TC development by knocking down UNC5B through upregulating the expression of miR‐129‐5p.